Wear-resistant and super-tough artificial stone plate as well as preparation method and application thereof
By using SiO2, CaCO3, MgO, Al2O3 and specific crystalline nucleation agents, the microcrystal sand and microcrystal powder are converted into amorphous amorphous silica material, which solves the problem of inhalable silica in artificial stone slabs, and achieves high-performance, wear-resistant and ultra-tough artificial stone slabs.
Patent Information
- Application Number
- CN202411815256.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-11
AI Technical Summary
The existing artificial stone slabs will produce inhalable crystalline silica during the production process, resulting in pneumoconiosis, and have low hardness, poor wear resistance and poor toughness, making it difficult to replace quartz stone.
Microcrystal sand and microcrystal powder are prepared by SiO2, CaCO3, MgO, Al2O3, flux, specific types of nucleation agents (such as ZrSiO4 and CaSiF6). Through high-temperature melting and crystallization treatment, it is converted into amorphous amorphous silicate material to avoid free inhalable silica.
The artificial stone slab without crystalline silica has been achieved, with good wear resistance, toughness and flexural strength, which solves the harm of pneumoconiosis in traditional quartz stone slabs, and improves the performance and market prospects of artificial stone slabs.
Smart Images

Figure BDA0005181579960000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of artificial stone, and particularly relates to a wear-resistant, super-tough artificial stone slab and a preparation method and application thereof. Background Art
[0002] Quartz is usually added to artificial stone slabs, but quartz produces inhalable crystalline silica during the production and grinding process, which can cause pneumoconiosis and pose a serious threat to people's health. Therefore, it is very important to find a suitable material that can replace quartz and then prepare quartz slabs.
[0003] At present, there are artificial stone slabs synthesized from amorphous materials such as glass sand powder obtained by recycling glass and crushing it, but this kind of artificial stone slab has the disadvantages of low hardness, poor wear resistance, poor toughness, the glass sand pink phase is blue-green and difficult to cover, and poor texture. In addition, glass sand powder contains a high content of strongly alkaline sodium oxide and potassium oxide. During the use of the countertop, the strongly alkaline sodium ions or potassium ions will react with water to precipitate strongly alkaline sodium or potassium ions, which will cause great corrosion to the resin in the artificial stone slab, and then cause discoloration and performance degradation, which is prone to quality problems and poor market recognition. Some studies have used methods such as calcining potassium-sodium feldspar to prepare quartz stone slabs. Because the quartz crystals are not completely converted into amorphous during the calcination process, only low-silicon quartz stone can be prepared, and there is still a large amount of free respirable crystalline silica (RCS). It is essentially quartz stone, and artificial stone made of feldspar is lower in hardness than quartz stone. In addition, calcined feldspar lacks transparency and jade-white color, which also limits the texture of the artificial stone produced. Only lower-grade artificial stone can be produced, and it is impossible to obtain high-end and wear-resistant artificial stone with fish belly white color and strong jade texture.
[0004] Therefore, it is of great significance to provide an artificial stone slab having good wear resistance, good toughness and no crystalline silica. Summary of the invention
[0005] The present invention aims to solve one or more technical problems existing in the above-mentioned prior art and at least provide a beneficial choice. Specifically, the present invention provides an artificial stone board, which has good wear resistance and toughness and does not contain crystalline silica.
[0006] The inventive concept of the present invention: the raw material components of the artificial stone slab of the present invention include microcrystalline sand, microcrystalline powder, resin, curing agent, coupling agent; the raw material components of the microcrystalline sand and microcrystalline powder include SiO2, CaCO3, MgO, Al2O3, flux, and nucleating agent; the nucleating agent includes ZrSiO4 and CaSiF6; the particle size of the microcrystalline sand is larger than the particle size of the microcrystalline powder. The present invention uses SiO2, CaCO3, MgO, Al2O3, flux, and a specific type of nucleating agent to prepare microcrystalline sand and microcrystalline powder. During the melting process of each raw material, the quartz crystal structure undergoes a qualitative change, the silicon-oxygen bond is opened, and elements such as aluminum, calcium, fluorine, and zirconium are embedded, especially fluorine-silicon bonds and high-content calcium oxide are obtained, and the structure is converted into a non-crystalline amorphous silicate material microcrystalline structure, and there is no free respirable silicon dioxide (RCS), which greatly reduces the harm of pneumoconiosis caused by crystalline silicon dioxide in traditional quartz slabs. At the same time, the pH of the aqueous solution of microcrystalline sand and microcrystalline powder is close to neutral (pH is about 7), which can avoid the damage and corrosion and discoloration of the binding resin in the artificial stone slab by strong alkaline raw materials such as high sodium, and combined with other components of the artificial stone slab, the artificial stone slab not only does not contain crystalline silica, but also has good wear resistance, toughness and flexural strength, resulting in a zero-quartz, wear-resistant, super-tough artificial stone slab.
[0007] Therefore, a first aspect of the present invention provides a wear-resistant, super-tough artificial stone slab.
[0008] Specifically, the raw material components of the wear-resistant and super-tough artificial stone slab include microcrystalline sand, microcrystalline powder, resin, curing agent, and coupling agent;
[0009] The raw material components of the microcrystalline sand and microcrystalline powder include SiO2, CaCO3, MgO, Al2O3, flux, and crystal nucleating agent;
[0010] The crystal nucleating agent includes ZrSiO4 and CaSiF6;
[0011] The particle size of the microcrystalline sand is larger than that of the microcrystalline powder.
[0012] Specifically, the nucleating agent can be divided into a type that reduces the crystallization temperature, a type that causes energy changes and spontaneous nucleation, a type that reduces activation energy, and a type that changes the network structure. The type of nucleating agent that reduces the crystallization temperature can reduce the temperature required for the material to crystallize, thereby accelerating the growth of the crystal; the type of nucleating agent that causes energy changes and spontaneous nucleation changes the energy state of the system so that the crystal spontaneously nucleates at a lower temperature; the type of nucleating agent that reduces activation energy can reduce the activation energy required for crystal growth, thereby accelerating the growth rate of the crystal; the type of nucleating agent that changes the network structure affects the precipitation and growth process of the crystal by changing the network structure of the material. The nucleating agent of the present invention is compounded with ZrSiO4 and CaSiF6, which has better effects in reducing the crystallization temperature, causing energy changes and spontaneous nucleation, reducing activation energy, and changing the network structure, so that the artificial stone board has a better semi-transparent milky effect, and better toughness and wear resistance.
[0013] Preferably, the mesh number of the microcrystalline sand is 6-200 mesh; further preferably, the mesh number of the microcrystalline sand is 6-180 mesh;
[0014] More preferably, the mesh size of the microcrystalline sand is 70-150 meshes.
[0015] Preferably, the mesh size of the microcrystalline powder is 300-850 mesh; further preferably, the mesh size of the microcrystalline powder is 325-800 mesh; further preferably, the mesh size of the microcrystalline powder is 325-500 mesh.
[0016] Preferably, in parts by weight, the raw material components of the microcrystalline sand and microcrystalline powder include 52-75 parts of SiO2, 9-20 parts of CaCO3, 3-11 parts of MgO, 3.5-16.5 parts of Al2O3, 0.1-2.2 parts of ZrSiO4, greater than 0.5 parts and less than or equal to 5.5 parts of CaSiF6, and 2-15.2 parts of flux.
[0017] Further preferably, the raw material components of the microcrystalline sand and microcrystalline powder include 58-70 parts of SiO2, 10-18 parts of CaCO3, 3-10 parts of MgO, 4-15 parts of Al2O3, 0.1-2 parts of ZrSiO4, greater than 0.5 parts and less than or equal to 5.5 parts of CaSiF6, and 2-14 parts of flux, in parts by weight.
[0018] Preferably, the flux includes at least one of Na2CO3, K2CO3, and B2O3.
[0019] Preferably, in parts by weight, the raw material components of the microcrystalline sand and microcrystalline powder include 52-75 parts of SiO2, 9-20 parts of CaCO3, 3-11 parts of MgO, 3.5-16.5 parts of Al2O3, 0.1-2.2 parts of ZrSiO4, greater than 0.5 parts and less than or equal to 5.5 parts of CaSiF6, 1-6.5 parts of Na2CO3, 1-6.5 parts of K2CO3, and 0-2.2 parts of B2O3.
[0020] Further preferably, the raw material components of the microcrystalline sand and microcrystalline powder include, by weight, 58-70 parts of SiO2, 10-18 parts of CaCO3, 3-10 parts of MgO, 4-15 parts of Al2O3, 0.1-2 parts of ZrSiO4, greater than 0.5 parts and less than or equal to 5 parts of CaSiF6, 1-6 parts of Na2CO3, 1-6 parts of K2CO3, and 0-2 parts of B2O3.
[0021] Specifically, the present invention can also calculate the amount of mineral raw materials (wollastonite, limestone, magnesite, alumina ore, soda ash, etc.) according to the mass ratio, and then use the mineral raw materials as raw material components for preparing microcrystalline sand and microcrystalline powder.
[0022] Preferably, the raw material components of the artificial stone slab include 40-65 parts of microcrystalline sand, 22-38 parts of microcrystalline powder, 9-18 parts of resin, 0.1-1.3 parts of curing agent, and 0.1-1.3 parts of coupling agent, by weight.
[0023] Further preferably, the raw material components of the artificial stone slab include 45-60 parts of microcrystalline sand, 25-35 parts of microcrystalline powder, 10-16 parts of resin, 0.1-1.2 parts of curing agent, and 0.1-1.2 parts of coupling agent, by weight.
[0024] Preferably, the raw material components of the artificial stone slab also include at least one of filler, color powder and color paste.
[0025] Preferably, the raw material components of the artificial stone slab also include fillers, color powders and color pastes, and by weight, the raw material components of the artificial stone slab include 40-65 parts of microcrystalline sand, 22-38 parts of microcrystalline powder, 9-18 parts of resin, 0.1-1.3 parts of curing agent, 0.1-1.3 parts of coupling agent, 0.45-1.1 parts of fillers, greater than 0 parts and less than or equal to 0.55 parts of color powder, and greater than 0 parts and less than or equal to 2.2 parts of color paste.
[0026] Further preferably, the raw material components of the artificial stone slab also include fillers, color powders and color pastes, and in parts by weight, the raw material components of the artificial stone slab include 45-60 parts of microcrystalline sand, 25-35 parts of microcrystalline powder, 10-16 parts of resin, 0.1-1.2 parts of curing agent, 0.1-1.2 parts of coupling agent, 0.5-1 part of filler, greater than 0 part and less than or equal to 0.5 part of color powder, and greater than 0 part and less than or equal to 2 parts of color paste.
[0027] Preferably, the resin includes at least one of unsaturated resin, epoxy resin and acrylic resin.
[0028] Preferably, the curing agent includes at least one of tert-butyl peroxide 2-ethylhexanoate, methyl ethyl ketone peroxide, tert-butyl perbenzoate, ethylenediamine, and diethylenetriamine.
[0029] Preferably, the coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.
[0030] Preferably, the filler comprises white corundum powder.
[0031] Preferably, the color paste includes at least one of titanium white paste, iron yellow paste, carbon black paste, scarlet paste and phthalocyanine blue paste.
[0032] Preferably, the color powder includes at least one of titanium dioxide, iron oxide red powder, iron oxide yellow powder, iron oxide black powder, phthalocyanine blue powder, metal powder and carbon black powder.
[0033] The second aspect of the present invention provides a method for preparing the wear-resistant and super-tough artificial stone slab described in the first aspect of the present invention.
[0034] Specifically, the method for preparing the wear-resistant and super-tough artificial stone slab comprises the following steps:
[0035] The various raw material components are mixed, formed, and cured to obtain the wear-resistant and super-tough artificial stone slab.
[0036] Preferably, the method for preparing the wear-resistant and super-tough artificial stone slab comprises the following steps:
[0037] (1) mixing the resin, filler, curing agent and coupling agent to obtain a premix;
[0038] (2) mixing the microcrystalline sand and microcrystalline powder with the premix obtained in step (1) to obtain a mixture;
[0039] (3) Adding the mixture obtained in step (2) to the mold backing plate, spraying the color powder and color paste, and then vacuuming, vibrating and curing to obtain the wear-resistant and super-tough artificial stone slab.
[0040] Preferably, the curing temperature is 110-125° C., and the curing time is 110-130 min; further preferably, the curing temperature is 115-120° C., and the curing time is 120-125 min.
[0041] Preferably, the method for preparing the microcrystalline sand and microcrystalline powder comprises the following steps:
[0042] (1) mixing the raw material components, melting, rolling and crystallizing to obtain a microchip;
[0043] (2) The microcrystalline chips obtained in step (1) are subjected to ball milling to different degrees to obtain the microcrystalline sand and microcrystalline powder.
[0044] Preferably, in step (1), the melting temperature is 1600-1750°C, and the melting time is 1.5-2.5h; further preferably, in step (1), the melting temperature is 1650-1750°C, and the melting time is 1.8-2.2h.
[0045] Preferably, in step (1), the temperature of the crystallization treatment is 750-1100°C, and the time of the crystallization treatment is 1.5-2.5h; further preferably, in step (1), the temperature of the crystallization treatment is 960-1100°C, and the time of the crystallization treatment is 1.8-2.2h.
[0046] Specifically, the crystallization process is a process of heat preservation and crystallization.
[0047] Preferably, the process of polishing, thickness determination and fine polishing is also included after curing.
[0048] The third aspect of the present invention provides an application of the artificial stone slab described in the first aspect of the present invention in the field of construction.
[0049] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0050] (1) The present invention uses SiO2, CaCO3, MgO, Al2O3, a cosolvent, and a specific type of nucleating agent to prepare microcrystalline sand and microcrystalline powder. During the melting process of each raw material, the quartz crystal structure undergoes a qualitative change, the silicon-oxygen bond is opened, and elements such as aluminum, calcium, fluorine, and zirconium are embedded, especially fluorine-silicon bonds and high-content calcium oxide are obtained, and the structure is converted into a non-crystalline amorphous silicate material microcrystalline structure. There is no free respirable silicon dioxide (RCS), which greatly reduces the harm of pneumoconiosis caused by crystalline silicon dioxide in traditional quartz slabs. At the same time, the pH of the microcrystalline sand and microcrystalline powder aqueous solution is close to neutral (pH is about 7), which can avoid the damage and corrosion discoloration of the high-sodium strong alkaline raw materials to the artificial stone slab binder resin, and combined with other components of the artificial stone slab, the artificial stone slab has good wear resistance, toughness and flexural strength on the basis of not containing crystalline silicon dioxide, and a zero-quartz, wear-resistant and ultra-tough artificial stone slab is obtained. It can replace quartz stone, glass sand powder artificial stone and calcined feldspar artificial stone. It is a new generation of high-performance artificial stone slabs with broad market application prospects.
[0051] (2) The present invention synthesizes the frit microcrystals by high-temperature melting, converts the quartz crystal components in the raw material into amorphous amorphous silicate structure microcrystal raw materials, and converts the raw materials containing free crystalline silicon dioxide (RCS) into amorphous microcrystal materials by melting and calcining, thereby greatly reducing the harm of quartz crystals that easily cause pneumoconiosis. At the same time, the pH, toughness and hardness of the microcrystal frit are controlled by the reasonable ratio of oxides, and a small amount of ultrafine white corundum powder is introduced when preparing artificial stone to promote filling density and further improve the wear resistance of artificial stone. DETAILED DESCRIPTION
[0052] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.
[0053] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0054] The raw material components and amounts of the microcrystalline sand and microcrystalline powder in Examples 1-4 are shown in Table 1.
[0055] Table 1: Raw material components and amounts of microcrystalline sand and microcrystalline powder in Examples 1-4 (parts by weight)
[0056] Raw material components Example 1 Example 2 Example 3 Example 4 <![CDATA[Al2O3]]> 5.0 7.5 9 11 <![CDATA[SiO2]]> 68.4 65.8 67 65.8 <![CDATA[CaCO3]]> 15.2 15.0 12.5 11 MgO 6.0 5.5 3.5 3.5 <![CDATA[Na2CO3]]> 3.0 2.5 3.5 2.0 <![CDATA[K2CO3]]> 1.0 1.5 1.8 2.5 <![CDATA[B2O3]]> 0.2 0.1 0.05 0.5 <![CDATA[CaSiF6]]> 0.9 1.8 2.2 3.0 <![CDATA[ZrSiO4]]> 0.1 0.2 0.3 0.5
[0057] Note: The raw material components and dosage of microcrystalline sand and microcrystalline powder are the same, the difference is the mesh size (different particle size).
[0058] Example 1
[0059] A wear-resistant and super-tough artificial stone plate comprises, by weight, 13 parts of isophthalic unsaturated resin, 56.2 parts of 100-mesh microcrystalline sand, 30 parts of 325-mesh microcrystalline powder, 0.15 parts of tert-butyl peroxide-2-ethylhexanoate, 0.15 parts of gamma-methacryloxypropyltrimethoxysilane, 0.5 parts of 3000-mesh white corundum powder, 0.2 parts of composite color powder A (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:1:2:1) and 1.2 parts of composite color paste B (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and bright red paste is 8:2:1:1).
[0060] The raw material components and dosage of microcrystalline sand and microcrystalline powder are shown in Table 1.
[0061] A wear-resistant and super-tough artificial stone slab comprises the following steps:
[0062] (1) placing raw material components of microcrystalline sand and microcrystalline powder into a frit furnace and heating to 1650° C., high temperature melting for 2 hours, pouring out and roller cooling into flakes, then heat preservation and crystallization in a crystallization roller kiln at 1000° C. for 2 hours, cooling, crushing, and then ball milling into 100 mesh microcrystalline sand and 325 mesh microcrystalline powder;
[0063] (2) mixing tert-butyl peroxy-2-ethylhexanoate, γ-methacryloxypropyltrimethoxysilane, white corundum powder and isophenyl unsaturated resin, stirring evenly to obtain a premix;
[0064] (3) mixing 100 mesh microcrystalline sand, 325 mesh microcrystalline powder and the premix obtained in step (2), rotating at a low frequency of 10 Hz for 2 minutes, rotating at a low frequency of 10 Hz for 2 minutes, rotating at a high frequency of 50 Hz for 3 minutes, rotating at a high frequency of 50 Hz for 3 minutes, and stirring and mixing for 10 minutes to obtain a mixture;
[0065] (4) adding the mixture obtained in step (3) to a mold backing plate and spraying the composite color powder and composite color paste; then feeding it into a press, evacuating the vacuum, and vibrating it in 8 frequency bands: 20 Hz / 40 seconds, 30 Hz / 30 seconds, 35 Hz / 30 seconds, 40 Hz / 30 seconds, 45 Hz / 60 seconds, and 50 Hz / 30 seconds for high frequency molding; then feeding the pressed plate into a curing furnace, curing it at 115° C. for 120 minutes, and then laying it flat for 24 hours to obtain a embryonic plate;
[0066] (5) After the embryonic plate obtained in step (4) is fed into a polishing machine to determine the thickness, fine polishing is performed using grinding blocks of 26, 46, 100, 300, 800, 1200, 1800, 3000, 5000, and 8000 meshes in sequence to obtain a wear-resistant and super-tough artificial stone plate.
[0067] Example 2
[0068] A wear-resistant and super-tough artificial stone plate comprises, by weight, 13 parts of isophthalic unsaturated resin, 56.2 parts of 100-mesh microcrystalline sand, 30 parts of 325-mesh microcrystalline powder, 0.15 parts of tert-butyl peroxide-2-ethylhexanoate, 0.15 parts of gamma-methacryloxypropyltrimethoxysilane, 0.5 parts of 3000-mesh white corundum powder, 0.3 parts of composite color powder C (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:1:3:1) and 1.5 parts of composite color paste D (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and bright red paste is 8:3:1:1).
[0069] The raw material components and dosage of microcrystalline sand and microcrystalline powder are shown in Table 1.
[0070] The preparation method of a wear-resistant and super-tough artificial stone slab is different from that of Example 1 only in that, in step (1) of Example 2, the raw material components of microcrystalline sand and microcrystalline powder are put into a frit furnace and heated to 1680° C., and in step (4), the raw material components are cured at 116° C. for 122 minutes and then laid flat for 24 hours.
[0071] Example 3
[0072] A wear-resistant and super-tough artificial stone plate comprises, by weight, 13 parts of isophthalic unsaturated resin, 56.2 parts of 100-mesh microcrystalline sand, 30 parts of 325-mesh microcrystalline powder, 0.15 parts of tert-butyl peroxide-2-ethylhexanoate, 0.15 parts of gamma-methacryloxypropyltrimethoxysilane, 0.5 parts of 3000-mesh white corundum powder, 0.25 parts of composite color powder E (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:1:1:2) and 1.6 parts of composite color paste F (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and bright red paste is 8:1:1:1).
[0073] The raw material components and dosage of microcrystalline sand and microcrystalline powder are shown in Table 1.
[0074] The preparation method of a wear-resistant and super-tough artificial stone slab is different from that of Example 1 only in that, in step (1) of Example 3, the raw material components of microcrystalline sand and microcrystalline powder are put into a frit furnace and heated to 1720° C., and in step (4), the raw material components are cured at 118° C. for 122 minutes and then laid flat for 24 hours.
[0075] Example 4
[0076] A wear-resistant and super-tough artificial stone plate comprises, by weight, 13 parts of isophthalic unsaturated resin, 56.2 parts of 100-mesh microcrystalline sand, 30 parts of 325-mesh microcrystalline powder, 0.15 parts of tert-butyl peroxide-2-ethylhexanoate, 0.15 parts of gamma-methacryloxypropyltrimethoxysilane, 0.5 parts of 3000-mesh white corundum powder, 0.13 parts of composite color powder F (the mass ratio of titanium dioxide, iron red powder, iron yellow powder and iron black powder is 5:1:1:3) and 1.7 parts of composite color paste G (the mass ratio of titanium white paste, iron yellow paste, carbon black paste and bright red paste is 8:1:1:2).
[0077] The raw material components and dosage of microcrystalline sand and microcrystalline powder are shown in Table 1.
[0078] The preparation method of a wear-resistant and super-tough artificial stone slab is different from that of Example 1 only in that, in step (1) of Example 4, the raw material components of microcrystalline sand and microcrystalline powder are put into a frit furnace and heated to 1750° C., and in step (4), the raw material components are cured at 120° C. for 125 minutes and then laid flat for 24 hours.
[0079] Comparative Example 1
[0080] Comparative Example 1 is an artificial stone slab synthesized using traditional recycled glass sand powder. The only difference between it and Example 1 is that Comparative Example 1 uses equal amounts of 100-mesh glass sand and 325-mesh glass powder to replace microcrystalline sand and microcrystalline powder respectively, and the rest is the same as Example 1.
[0081] Comparative Example 2
[0082] Comparative Example 2 is an artificial stone slab synthesized using traditional quartz sand and powder. The only difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses equal amounts of 100-mesh quartz sand and 325-mesh quartz powder to replace microcrystalline sand and microcrystalline powder respectively, and the rest is the same as Example 1.
[0083] Comparative Example 3
[0084] The difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses an equal amount of ZnO to replace ZrSiO4 in Example 1, and the rest is the same as Example 1.
[0085] Comparative Example 4
[0086] The difference between Comparative Example 4 and Example 1 is that Comparative Example 4 uses an equal amount of CaF2 to replace the CaSiF6 of Example 1, and the rest is the same as Example 1.
[0087] Performance Testing
[0088] The performance tests were conducted on the artificial stone panels of Examples 1-4 and Comparative Examples 1-4. The test items and test methods are as follows:
[0089] Appearance: Visual;
[0090] Flexural strength, Mohs hardness, abrasion resistance, falling ball impact strength: measured in accordance with JC / T 908-2013;
[0091] Respirable crystalline silica (RCS) content: tested by X-ray diffraction (XRD) method.
[0092] The test results of the performance of the artificial stone panels of Examples 1-4 and Comparative Examples 1-4 are shown in Table 2.
[0093] Table 2: Test results of artificial stone slab performance of Examples 1-4 and Comparative Examples 1-4
[0094]
[0095] It can be seen from Table 2 that the artificial stone slab prepared by the present invention has good toughness and wear resistance, and does not contain crystalline silica. It is a zero-quartz, wear-resistant, super-tough artificial stone slab with great value and market prospects. At the same time, its appearance is slightly milky white and semi-transparent, and its texture is strong.
[0096] Comparative Example 1 uses an equal amount of 100 mesh glass sand and 325 mesh glass powder to replace microcrystalline sand and microcrystalline powder, respectively, so that the flexural strength, Mohs hardness, wear resistance, and falling ball impact strength of Comparative Example 1 are significantly worse than those of Example 1, and the texture is poor. Comparative Example 2 uses an equal amount of 100 mesh quartz sand and 325 mesh quartz powder to replace microcrystalline sand and microcrystalline powder, respectively, so that the flexural strength, wear resistance, and falling ball impact strength of Comparative Example 2 are significantly worse than those of Example 1, the texture is poor, and the content of inhalable crystalline silica is relatively high. Comparative Examples 1 and 2 illustrate that the present invention uses specific microcrystalline sand and microcrystalline powder to have good toughness and wear resistance, and does not contain crystalline silica, and has a strong texture.
[0097] Comparative Example 3 uses an equal amount of ZnO to replace ZrSiO4 in Example 1, and Comparative Example 4 uses an equal amount of CaF2 to replace CaSiF6 in Example 1, and the rest is the same as Example 1, so that the flexural strength, wear resistance, and falling ball impact strength of Comparative Examples 3 and 4 are significantly worse than those of Example 1, and the texture is poor. Comparative Examples 3 and 4 illustrate that the use of a specific compound of CaSiF6 and ZrSiO4 in the present invention has better effects in reducing crystallization temperature, causing energy changes and spontaneous nucleation, reducing activation energy, and changing network structure, thereby making the artificial stone board have better semi-transparent milky effect, better toughness and wear resistance.
[0098] In summary, the present invention uses SiO2, CaCO3, MgO, Al2O3, a cosolvent, and a specific type of nucleating agent to prepare microcrystalline sand and microcrystalline powder. During the melting process of each raw material, the quartz crystal structure undergoes a qualitative change and is converted into an amorphous silicate material microcrystalline structure, without free inhalable silicon dioxide. At the same time, it can avoid the damage and corrosion discoloration of the artificial stone plate binding resin by high sodium strong alkaline raw materials, and combined with other components of the artificial stone plate, the artificial stone plate has good wear resistance, toughness and flexural strength on the basis of not containing crystalline silicon dioxide, and can replace quartz stone, glass sand powder artificial stone and calcined feldspar artificial stone, and has broad market application prospects.
[0099] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the protection scope of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. An artificial stone slab, characterized in that: Its raw material components include microcrystalline sand, microcrystalline powder, resin, curing agent, coupling agent; The raw material components of the microcrystalline sand and microcrystalline powder include SiO2, CaCO3, MgO, Al2O3, flux, and crystal nucleating agent; The crystal nucleating agent includes ZrSiO4 and CaSiF6; The particle size of the microcrystalline sand is larger than that of the microcrystalline powder.
2. The artificial stone slab according to claim 1, characterized in that: The mesh size of the microcrystalline sand is 6-200 meshes; and / or, the mesh size of the microcrystalline powder is 300-850 meshes; and / or, the flux includes at least one of Na2CO3, K2CO3, and B2O3.
3. The artificial stone slab according to claim 1, characterized in that: In terms of weight, the raw material components of the microcrystalline sand and microcrystalline powder include 52-75 parts of SiO2, 9-20 parts of CaCO3, 3-11 parts of MgO, 3.5-16.5 parts of Al2O3, 0.1-2.2 parts of ZrSiO4, greater than 0.5 parts and less than or equal to 5.5 parts of CaSiF6, and 2-15.2 parts of flux.
4. The artificial stone slab according to claim 1, characterized in that: Calculated by weight, the raw material components of the artificial stone slab include 40-65 parts of microcrystalline sand, 22-38 parts of microcrystalline powder, 9-18 parts of resin, 0.1-1.3 parts of curing agent, and 0.1-1.3 parts of coupling agent.
5. The artificial stone slab according to claim 1, characterized in that: The raw material components of the artificial stone slab also include at least one of filler, color powder and color paste.
6. The artificial stone slab according to claim 5, characterized in that: The raw material components of the artificial stone slab also include fillers, color powders and color pastes, and by weight, the raw material components of the artificial stone slab include 40-65 parts of microcrystalline sand, 22-38 parts of microcrystalline powder, 9-18 parts of resin, 0.1-1.3 parts of curing agent, 0.1-1.3 parts of coupling agent, 0.45-1.1 parts of fillers, greater than 0 parts and less than or equal to 0.55 parts of color powder, and greater than 0 parts and less than or equal to 2.2 parts of color paste.
7. The artificial stone slab according to claim 5, characterized in that: The resin includes at least one of unsaturated resin, epoxy resin, and acrylic resin; and / or, the curing agent includes at least one of tert-butyl peroxide 2-ethylhexanoate, methyl ethyl ketone peroxide, tert-butyl perbenzoate, ethylenediamine, and diethylenetriamine; and / or, the coupling agent includes at least one of γ-methacryloxypropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, and γ-aminopropyltriethoxysilane; and / or, the filler includes white corundum powder; and / or, the color paste includes at least one of titanium white paste, iron yellow paste, carbon black paste, scarlet paste, and phthalocyanine blue paste; and / or, the color powder includes at least one of titanium white powder, iron red powder, iron yellow powder, iron black powder, phthalocyanine blue powder, metal powder, and carbon black powder.
8. The method for preparing the artificial stone slab according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw material components are mixed, formed and cured to obtain the artificial stone slab.
9. The preparation method according to claim 8, characterized in that: The method for preparing the microcrystalline sand and microcrystalline powder comprises the following steps: (1) mixing the raw material components, melting, rolling and crystallizing to obtain a microchip; (2) The microcrystalline chips obtained in step (1) are subjected to ball milling to different degrees to obtain the microcrystalline sand and microcrystalline powder.
10. Use of the artificial stone slab according to any one of claims 1 to 7 in the field of construction.
Citation Information
Patent Citations
Artificial stone and production method thereof
CN104529379A
Flexible artificial leather and preparation method thereof
CN108219485A
Production of granitic artificial stone
JP1990102155A
Nozzle for casting
JP1994015422A
Composition for coating material
JP1999217540A
Cited By
Artificial environment-friendly zero-crystalline silicon quartz stone forming process and manufacturing equipment thereof
CN119974576A
Artificial Environmentally Friendly Zero-Crystallization Quartz Stone Molding Process and Its Manufacturing Equipment
CN119974576B